Peningkatan Minat Pemeriksaan Penyakit Tidak Menular pada Remaja melalui Edukasi Kesehatan - Sheila Ridhawaty; Maranata Maranata; Marlin Brigita; Achmad Rizki Azhari; Muhammad Luthfi Abdul Ghaffar (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Noncommunicable diseases may arise from risk factors established during adolescence, while awareness of early detection remains low because screening is often considered necessary only for adults. This community service activity aimed to increase adolescents’ interest in early detection screening for noncommunicable diseases through health education. The activity involved 31 eleventh-grade health students at SMK ICB Cinta Teknika and used classroom counseling supported by PowerPoint and posters. Students’ interest was assessed before and after education. Before the activity, only two female students were interested, while no male students expressed interest. After the intervention, 27 students were willing to undergo screening, comprising two male and 25 female students, whereas two female students remained uninterested. These findings indicate that health education can increase adolescents’ interest in early detection of noncommunicable diseases and support school-based promotive and preventive strategies.